The Effect of Benzyl Amino Purin and NaphtalenaAcetic Acid Applications on Direct Shoot Organogenesis in Porang (Amorphophallus muelleri B) - Restanto, Didik Pudji; Aji, Seto Purnomo; Handayani, Etty; Ratnasari, Tri; Jadmiko, Mochammad Wildan; Prayoga, Mohammad Candra; Khozin, Mohammad Nur; Kriswanto, Budi (PLANTA TROPIKA, 2024)
Porang (Amorphophallus muelleri B.) is a tuberous plant with the potential to be the main source of carbohydrates and is rich in benefits. Porang proliferation is limited by a 6-month dormancy period per year, and generative propagation is unlikely due to the seeds being apomictic triploid. The aimed of my research to analyze the application of BAP and NAA in culture media for direct propagation of porang shoots. The explant used in this research was young leaves. The research was arranged in a completely randomized design with a combination of BAP and NAA hormones added to the MS medium. There were three BAP treatments, namely 1.0 mg/L, 2.0 mg/L, and 3.0 mg/L, while NAA treatments consisted of 2 levels, namely 2.0 mg/L and 4.0 mg/L. The addition of 1.0 mg/L BAP combined with 4.0 mg/L NAA was the best treatment that produced seven shoots with an average shoot length of 2.14 cm and root length of 3.6 cm, with the earliest bud emergence (9.7 weeks after planting).